The treatment of acute promyelocytic leukemia in 2023: Paradigm, advances, and future directions - Iyer, Sunil Girish; Elias, Laila; Stanchina, Michele; Watts, Justin (Frontiers in Oncology, 2023)
The transformation of acute promyelocytic leukemia (APL) from an often fatal to highly curable cancer with long-term survival exceeding 90% is one of the greatest and most inspiring successes in oncology. A deeper understanding of the pathogenesis of APL heralded the introduction of highly effective therapies targeting the mutant protein that drives the disease, leading to the chemotherapy-free approach to cure almost all patients. In this review, we discuss the paradigm of treatment of APL in 2023, reinforce the high risk of early death without prompt initiation of treatment at first clinical suspicion, and dedicate a special focus to novel agents and future directions to improve cure rates and quality of life in patients affected by APL.